Protein-specific immune response elicited by the Shigella sonnei 1790GAHB GMMA-based candidate vaccine in adults with varying exposure to Shigella - Arlo Z. Randall; Valentino Conti; Usman Nakakana; Xiaowu Liang; Andy A. Teng; Antonio Lorenzo Di Pasquale; Melissa Kapulu; Robert Frenck; Odile Launay; Pietro Ferruzzi; Antonella Silvia Sciré; Elisa Marchetti; et al. (mSphere)
ABSTRACT Shigella is a leading cause of diarrheal morbidity and mortality in young children from low- and middle-income countries. Here, we aimed to verify the ability of the generalized modules for membrane antigens (GMMA)-based Shigella sonnei candidate vaccine 1790GAHB to elicit an anti-protein antibody response. Serum samples from previous clinical trials in adults (a dose-escalation study and its extension in France, a vaccine efficacy study after human challenge in the United States, and a study in Kenya) were investigated using pan-proteome microarrays consisting of 3,150 full-length or fragmented Shigella proteins. Pre-/post-vaccination comparisons identified subsets of proteins that were highly immunoreactive and largely overlapped across all trials; the T3SS lipochaperone family protein (expressed on GMMA) was the most reactive in all studies. Responses to several microarray antigens correlated well with S. sonnei LPS serum IgG antibody levels. Overall, we confirmed the ability of GMMA to elicit an anti-protein IgG/IgA response; however, no association with protection against shigellosis was identified. In the challenge study, IgG response to seven antigens (IpaC, IpaB, IpaA, IpaD, IpaH, IpgC, and MxiD; not expressed on GMMA) was associated with a decreased risk of shigellosis. These antigens were observed to also have high IgG responses at baseline in individuals naturally exposed to Shigella and could constitute targets for future vaccine development.IMPORTANCEShigella remains a major cause of diarrheal disease, especially in children aged under 5 years from low-to-middle-income countries. No vaccine against shigellosis is yet widely available despite the high public health need. An ideal vaccine would provide protection against the most prevalent species, Shigella flexneri and Shigella sonnei; therefore, it could be relevant to identify common antigens. We developed a microarray containing 3,150 full-length or fragmented proteins selected across Shigella species. Sera collected in four clinical trials conducted in three countries of varying endemicity to evaluate a S. sonnei GMMA-based candidate vaccine were tested against these proteins. We identified several Shigella proteins (IpaC, IpaB, IpaA, IpaD, IpaH, IpgC, MxiD) that induced robust antibody response following experimental challenge or natural infection. These proteins correlated with a reduced risk of shigellosis after the S. sonnei challenge. We found no apparent role for anti-GMMA proteins’ IgG or IgA response in protection against shigellosis.